Micromagnetic simulation of magnetic domain structures evolution of FeGa alloys by phase-field method - Lu, Yanli; Guo, Runan; Zhang, Tinghui; Chen, Zheng (Materials science & engineering. B, Solid-state materials for advanced technology, 2020)
[Display omitted] •Predicted domain structures evolution by micromagnetic model and phase-field method.•Magnetization vectors will parallel to the external magnetic field when the direction of external magnetic field is [1 0 0].•When the direction of external magnetic field is [1 1 1], the system will form the stable striped domains structure.•The curves of total free energy changes of the system during the evolution are shown in this paper. The stabilization of magnetic domains and their temporal evolution in FeGa alloys are predicted by combining micromagnetic model with phase-field method in this paper. The total free energy includes magnetocrystalline anisotropy energy, exchange energy, magnetostatic energy, external field energy and elastic energy. Under the diverse magnetic fields, domain structures are various because of the different total free energy and magnetization processes. The results show that when magnetic field direction along [1 0 0], with different magnetic strength, the directions of magnetization vectors all parallel to the magnetic field direction and the magnetized area forms a single domain structure eventually. When the magnetic field along [1 1 1] direction, the magnetic domains form striped domains. The direction and strength of magnetic field can effectively control the structures of magnetic domains. The total free energy increases with the increase of magnetic field strength and evolutionary steps. The system is stable with the stabilization of total free energy.